2010
DOI: 10.1007/s00586-010-1657-6
|View full text |Cite
|
Sign up to set email alerts
|

Back pain in adolescents with idiopathic scoliosis: epidemiological study for 43,630 pupils in Niigata City, Japan

Abstract: There have been a few studies regarding detail of back pain in adolescents with idiopathic scoliosis (IS) as prevalence, location, and severity. The condition of back pain in adolescents with IS was clarified based on a crosssectional study using a questionnaire survey, targeting a total of 43,630 pupils, including all elementary school pupils from the fourth to sixth grade (21,893 pupils) and all junior high pupils from the first to third year (21,737 pupils) in Niigata City (population of 785,067), Japan. 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 21 publications
1
61
1
5
Order By: Relevance
“…[1][2][3] Adolescents with AIS also encounter more severe pain of longer duration with more frequent recurrences than controls. 1 Authors of a retrospective study of AIS reported that back pain is prevalent in adolescents who are older than 15 years, whose skeletal maturity yields a Risser sign of 2 or more, are postmenarchal, and have a history of injury. Conversely, no association with sex, family history of scoliosis, limb-length discrepancy, magnitude or type of curve, or spinal alignment was noted.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3] Adolescents with AIS also encounter more severe pain of longer duration with more frequent recurrences than controls. 1 Authors of a retrospective study of AIS reported that back pain is prevalent in adolescents who are older than 15 years, whose skeletal maturity yields a Risser sign of 2 or more, are postmenarchal, and have a history of injury. Conversely, no association with sex, family history of scoliosis, limb-length discrepancy, magnitude or type of curve, or spinal alignment was noted.…”
Section: Introductionmentioning
confidence: 95%
“…5 Although it is not the main clinical factor, patients with AIS may have pain; they are more prone to pain when the degree of Cobb's angle is higher. 6 Studies on AIS prevalence have demonstrated that between 27% and 59% of patients suffer pain.…”
Section: Introductionmentioning
confidence: 99%
“…6 Studies on AIS prevalence have demonstrated that between 27% and 59% of patients suffer pain. 5,7 In addition, it may be associated with other conditions, such as restricted ventilation, respiratory muscle weakness, reduced quality of life, 8 and even psychological problems. 9 At present, according to the 2016 AIS consensus, 1 follow-up and management include observation, bracing or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…De todo el conjunto de problemas que se desarrollan en la infancia, no cabe duda que uno de ellos, la escoliosis, es fuente de preocupación en aquellos padres que comienzan a observar con el transcurso del tiempo como sus hijos pueden terminar desarrollando este tipo de patología, asociada en ocasiones a sintomatología dolorosa (Sato et al, 2011). Dentro del gran número de clasificaciones de escoliosis que podemos encontrar en la literatura científica, la Sociedad para el Estudio de las Enfermedades del Raquis la define como una desviación lateral del raquis con manifestaciones clínicas visibles relacionadas con desplazamiento lateral de la columna vertebral, asociada a la rotación de las vértebras implicadas (Zurita Ortega et al, 2008a).…”
Section: Introductionunclassified